Clinical epidemiological survey of gallbladder carcinoma in northwestern China, 2009â2013: 2379 cases in 17 centers - Hao-Xin Shen (KeAi Communications Co., Ltd., 2017)
Objective: To analyze the clinical epidemiological characteristics of patients with gallbladder carcinoma recruited from 17 hospitals in five northwestern provinces of China (Shaanxi Province, Gansu Province, Qinghai Province, Ningxia Hui Autonomous Region, and Xinjiang Uygur Autonomous Region) from 2009 to 2013, and to summarize the clinical diagnosis and treatment data of gallbladder carcinoma. Methods: Clinical information of 2379 patients with gallbladder carcinoma from 17 hospitals in five northwestern provinces of China was retrospectively collected and analyzed using the âQuestionnaire for Gallbladder Carcinoma Patients in Northwestern Area of China.â All information was verified with EpiData software and analyzed with SPSS 13.0 software. Results: (1) Gallbladder carcinoma accounted for 2.7% (2379/86,609) of all biliary tract diseases during the study period, which was significantly higher than that from 1986 to 1998 (PÂ <Â 0.001). (2) Gallbladder carcinoma was more prone to occur in elderly women. The male:female incidence ratio was 1.0:2.1, the average age of onset of disease was 63.7Â Â±Â 11.3 years, and the incidence was higher in farmers than in other occupational groups. (3) A total of 57.2% (1360/2379) of patients with gallbladder carcinoma also had gallstones. (4) Abdominal pain (1796/2379, 75.5%) and jaundice (727/2379, 30.6%) were the most common clinical manifestations, 81.2% (1527/1881) were positive in those receiving B ultrasound examinations and 90.7% (1567/1727) were positive in those undergoing computed tomography, and 64.5% (1124/1742) of patients with gallbladder carcinoma were positive for carbohydrate antigen (CA) 19-9. (5) The pathological type of gallbladder carcinoma was mainly moderately and poorly differentiated adenocarcinoma with a high degree of malignancy. At admission, 55.1% (1091/1981) of patients had stage IV cancer among patients with TNM staging information; 55.9% (1331/2379) had lymphatic metastasis, 29.7% (706/2379) had bile duct metastasis, and 53.1% (1263/2379) had liver metastasis. (6) A total of 283 patients (283/2379, 11.9%) had incidentally detected gallbladder carcinoma. (7) The rate of radical surgical resection was 30.4% (723/2379). Conclusion: The proportion of gallbladder carcinoma in biliary tract diseases in the northwestern area of China was significantly higher from 2009 to 2013 than from 1986 to 1998. Gallbladder carcinoma was common in older women and mainly diagnosed at an advanced stage. Compared with other surveys in different regions, the rate of metastasis in this survey was high, leading to a low resection rate. Populations at high risk should undergo B-ultrasound examinations at regular follow-up intervals to increase the rate of early diagnosis of gallbladder carcinoma. Keywords: Gallbladder carcinoma, Epidemiology, Incidence, Risk factor, Northwestern China